From Pain Patient to Junkie: An Economic Theory of Painkiller Consumption and its Impact on Wellbeing and Longevity - Holger Strulik (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
In this paper, I propose a life cycle model of painkiller consumption that combines the theory of health deficit accumulation with the theory of addiction. Chronic pain is conceptualized as a persistent negative shock to lifetime utility that can be treated by pain relief medication. Some individuals treated with opioid pain relievers develop addiction, which increases their demand for opioids and reduces their welfare and life expectancy through side effects and potential overdose. Nevertheless, individuals prefer opioid treatment if they fail to understand how it causes addiction. Once individuals are unintentionally addicted and access to prescription opioids is discontinued, consumption shifts to illicit opioids (like heroin). I calibrate the model for a benchmark American and investigate the comparative dynamics of alternative drug characteristics, pain intensities, and ages of onsets of pain and their implications for welfare and life expectancy. I also discuss treatment of addiction and the use of opioids in palliative care.
Keywords: D15; 330; pain; pain relief; addiction; opioid epidemic; health deficits; life expectancy; illicit drugs